História, narrativa gráfica e a ditadura militar em Belém: presente, passado e futuro pela ótica da arte sequencial - ARAÚJO, Plínio Sá de (Universidade Federal do Pará, 2019)
The dissertation proposal is based on the research line Historical Languages and Narratives: Production and Diffusion, of the Professional Master's Degree in History Teaching (PROFHISTÓRIA). The essay body is divided into four interrelated chapters aiming at the methodology of history teaching practices, using comics as a literary genre capable of narrating long-lasting stories. For this, the work is based on the dialogue between characteristics of semiotics, typical of comics, combined with propositions of the theory of history as historical narrative, historical consciousness and historical learning. The accomplishment of this dialogue is allied to debates and research workshops held at the Ruth dos Santos Almeida School, in the National Curricular Parameters and in the historiographic clipping that precedes and initiates the Civil-Military Dictatorship, in Belém, 1964. The result of the debate of these propositions presents as a HQ product.